Morin Flavonoid Interaction with Albumin and Its Nanoparticle Conjugation: An Efficient Antioxidant Vehicle for Nutraceuticals - Sandoval-Altamirano, C (Multidisciplinary Digital Publishing Institute (MDPI), 2025)
Morin is a natural flavonoid with potent antioxidant activity, yet its clinical and nutraceutical applications remain limited due to poor aqueous solubility and low bioavailability. This study explores the interaction of morin with bovine serum albumin (BSA) and the development of BSA-based nanoparticles as a delivery platform. Fluorescence spectroscopy confirmed the formation of a stable 1:1 morin–BSA complex, governed by hydrophobic interactions, with a binding constant (Ka) of 1.87 × 105 L·mol−1. Binding conferred enhanced photostability, as BSA attenuated morin degradation under oxidative stress conditions. BSA nanoparticles prepared by desolvation encapsulated morin with high monodispersity and encapsulation efficiencies up to 26%. Co-encapsulation with ellagic acid or tocopherol succinate improved loading capacity but reduced morin release, suggesting intermolecular stabilization. Release studies in simulated intestinal fluid showed controlled diffusion, while compatibility assays in milk-based food matrices confirmed colloidal stability in whole and reduced-fat milk. These findings support BSA–morin nanoparticles as a promising system for the oral delivery and functional food incorporation of polyphenolic antioxidants. © 2025 by the authors.